Working dogs transfer different tasks in reciprocal cooperation. (28th February 2018) - Gfrerer, Nastassja; Taborsky, Michael
Abstract : Direct reciprocity can establish stable cooperation among unrelated individuals. It is a common assumption of direct reciprocity models that agents exchange like with like, but this is not necessarily true for natural interactions. It is yet unclear whether animals apply direct reciprocity rules when successive altruistic help involves different tasks. Here, we tested whether working dogs transfer help from one to another cooperative task in an iterated prisoner's dilemma paradigm. In our experiment, individual dogs received help to obtain food from a conspecific, which involved a specific task. Subsequently, the focal subject could return received favour by using a different task. Working dogs transferred the cooperative experience received through one task by applying an alternative task when they helped a previously cooperative partner. By contrast, they refrained from helping previously defecting partners. This suggests that dogs realize the cooperative act of a conspecific, which changes their propensity to provide help to that partner by different means. The ability of animals to transfer different tasks when helping a social partner by satisfying the criteria of direct reciprocity might explain the frequent occurrence of reciprocal cooperation in nature.